2019
DOI: 10.1111/1365-2435.13353
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐off or coordination? Correlations between ballochorous and myrmecochorous phases of diplochory

Abstract: The combination of two dispersal syndromes (diplochory) brings additional benefits to seeds, yet the relative costs and benefits of the two phases are poorly understood. Our goal is to provide the first quantification to test the long‐standing assumption that there are trade‐offs between the two phases in ballistic–ant diplochory. Dispersal investment data were empirically measured for 91 Euphorbiaceae species across different regions of the world. Dispersal distance data of ballochory (seed dispersal by explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 57 publications
0
20
0
1
Order By: Relevance
“…Large seeds are maladaptive for longdistance dispersal under the same condition with the dispersal of small seeds (Thomson et al 2011). However, the dispersal difficulties for species with large seeds are often counterbalanced by their advantages on seed release height, resource allocation and dispersal mode (Thomson et al 2011;Chen et al 2019a). This leads to the discrepancy of the lasting assumption that large seeds face difficulties of dispersal potential and the fact that large seeds actually reach further dispersal distances than small seeds (Thomson et al 2011), as shown in our SEM models.…”
Section: Seed Massmentioning
confidence: 88%
“…Large seeds are maladaptive for longdistance dispersal under the same condition with the dispersal of small seeds (Thomson et al 2011). However, the dispersal difficulties for species with large seeds are often counterbalanced by their advantages on seed release height, resource allocation and dispersal mode (Thomson et al 2011;Chen et al 2019a). This leads to the discrepancy of the lasting assumption that large seeds face difficulties of dispersal potential and the fact that large seeds actually reach further dispersal distances than small seeds (Thomson et al 2011), as shown in our SEM models.…”
Section: Seed Massmentioning
confidence: 88%
“…It is worth noting that the regression slopes of seed mass variability were statistically different among dispersal modes in our study. This could be explained by different seed mass allocation strategies among dispersal modes (Chen et al, 2018;Chen et al, 2019a).…”
Section: Effects Of Dispersal Modes and Seed Mass On The Distributionmentioning
confidence: 99%
“…However, we know little about the effects of dispersal modes on species distribution. Furthermore, because dispersal modes are often related to seed mass variation (Moles et al, 2007;Chen et al, 2019a), discerning the relative importance of seed mass and dispersal on the geographic distribution of seed plants is important but elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there was an increase in dispersal distance due to the presence of Myrmica ants. Thus, V. riviniana can be clearly referred to as a diplochorous species producing seeds that are primarily dispersed ballochorously (seed dispersal by explosion) and that might occasionally be picked up and carried by ants afterwards [35]. The genus Viola comprises a set of myrmecochorous species with large elaiosomes, comparable to Scilla or Corydalis in our study, and a set of ballistic diplochorous species with rather small elaiosomes, like the Northern American Common Violet (Viola papilionacea Pursh [36]), or our Central European Viola riviniana.…”
Section: Viola Rivinianamentioning
confidence: 99%